2019
DOI: 10.1111/jnc.14647
|View full text |Cite
|
Sign up to set email alerts
|

A novel crosslinking protocol stabilizes amyloid β oligomers capable of inducing Alzheimer's‐associated pathologies

Abstract: Amyloid β oligomers (AβOs) accumulate early in Alzheimer's disease (AD) and experimentally cause memory dysfunction and the major pathologies associated with AD, for example, tau abnormalities, synapse loss, oxidative damage, and cognitive dysfunction. In order to develop the most effective AβO‐targeting diagnostics and therapeutics, the AβO structures contributing to AD‐associated toxicity must be elucidated. Here, we investigate the structural properties and pathogenic relevance of AβOs stabilized by the bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 66 publications
2
26
0
2
Order By: Relevance
“…Other protocols relied on the use of chemical or radical-mediated crosslinking approaches to trap and/or stabilize transient oligomers to facilitate their characterization or isolation. [180][181][182][183][184][185][186] At the structural level, on-pathway oligomers tend to exhibit a mixture of secondary structure contents, [187][188][189] often dominated by b-sheet conformations. 190 Compared to amyloid fibrils, oligomeric intermediates of most amyloid forming proteins exhibit weak binding to the amyloid specific dyes thioflavin T/S (ThT/S) and Congo red, 191,192 suggesting that they have not acquired the cross-b structure that is characteristic of amyloid fibrils, although studies on Ab oligomers using X-ray fiber diffraction have suggested that some oligomers possess cross-b-like conformations.…”
Section: The ''Oligomer Hypothesis''mentioning
confidence: 99%
“…Other protocols relied on the use of chemical or radical-mediated crosslinking approaches to trap and/or stabilize transient oligomers to facilitate their characterization or isolation. [180][181][182][183][184][185][186] At the structural level, on-pathway oligomers tend to exhibit a mixture of secondary structure contents, [187][188][189] often dominated by b-sheet conformations. 190 Compared to amyloid fibrils, oligomeric intermediates of most amyloid forming proteins exhibit weak binding to the amyloid specific dyes thioflavin T/S (ThT/S) and Congo red, 191,192 suggesting that they have not acquired the cross-b structure that is characteristic of amyloid fibrils, although studies on Ab oligomers using X-ray fiber diffraction have suggested that some oligomers possess cross-b-like conformations.…”
Section: The ''Oligomer Hypothesis''mentioning
confidence: 99%
“…While, STS pretreatment decreased the levels of ROS, MDA, NO and iNOS, and increased the activities of SOD and GSH‐Px significantly. In addition, Aβ accumulation can also induce neuroinflammation in the AD patients' brain . In this study, Aβ‐treatment increased the neuroinflammatory factors (IL‐1β, IL‐6 and TNF‐α) in SH‐SY5Y cells.…”
Section: Resultsmentioning
confidence: 51%
“…In addition, Aβ accumulation can also induce neuroinflammation in the AD patients' brain. 26,27 In this study, Aβ-treatment increased the neuroinflammatory factors (IL-1β, IL-6 and TNF-α) in SH-SY5Y cells. Sodium tanshinone IIA sulfonate pretreatment significantly decreased these neuroinflammatory factors (Figure 4).…”
Section: Sts Ameliorates Oxidative Stress Nitrosative Stress and Nmentioning
confidence: 48%
“…Com o intuito de avaliar o peso molecular da espécie de AβOs alvo de NUsc1 sem possíveis artefatos introduzidos pela influência do SDS (no SDS-PAGE) sobre o estado oligomérico dos AβOs, foi utilizado uma preparação de AβOs estabilizados por crosslinking (AβOs-XL) utilizando o reagente DFDNB. AβOs preparados por esse protocolo foram recentemente descritos como estáveis em SDS, e neurotóxicos (CLINE et al, 2019). Beads funcionalizadas com NUsc1 e bloqueadas com BSA foram incubadas com AβOs-XL, e o complexo AβOsXL-NUsc1 resultante foi eluido e analisado por western blotting utilizando o anticorpo anti-AβOs NU2 (Fig.…”
Section: Isolamento De Aβos Estabilizados Por Crosslinking Usando Nusunclassified
“…Este dado contribui significativamente com a determinação da seletividade por massa molecular dos oligômeros reconhecidos por NUsc1. Além disso, esse achado também contribui para a validação dos AβOs-XL como uma preparação na qual as espécies estabilizadas por crosslinking preservam epítopos conformacionais encontrados nos AβOs tóxicos (CLINE et al, 2019).…”
Section: Determinação Do Peso Molecular Do Complexo Aβos-nusc1 Por Crunclassified